Kierkegaard's Relation to Catholic Theology and the Broader Christian World - Evans, C. Stephen (Toronto journal of theology, 2016)
This article responds to articles by Joshua Furnal and Lee Barrett on the relation of Kierkegaard's thought to Catholic theology. I express appreciation for Furnal's claim that Kierkegaard had a deep impact on Vatican ii and suggest this was made possible by Kierkegaard's commitment to the early Christian fathers, which makes him a "ressourcement" theologian. Barrett's view of Kierkegaard's account of the relation between nature and grace is also applauded, and I suggest another way Kierkegaard can be seen as reconciling Protestant and Catholic thought on this issue. I conclude by putting this discussion into the broader context of Kierkegaard's positive reception by many different strands of Christianity, suggesting that this is made possible by Kierkegaard's commitment to something like "mere Christianity" in C.S. Lewis's sense, along with his fervent defence of passion and subjectivity as the elements that give life to religious faith.